Perception of advisors' regarding behaviour of investors' while selecting wealth management services: an AHP approach. (2018) - Arora, Ashish; Verma, Rashim
Significant contributing factor for the growth of WMS can be global increase of wealth, especially India and China given the vigorous boost to the wealth. Also the need of the clients extends far beyond the old stock picking, rather becoming more sophisticated, requiring more exciting products and services. Having anticipated significant increase in number of high net worth (HNW) clients and their diverse investment requirements, financial intermediaries comprising of bank financial advisers (BFA), independent financial advisers (IFA) and corporate financial advisers (CFA) began offering investment advisory services to HNW under the umbrella of WMS and there is significant change in their investment strategies. Study of wealth management industry has become significant owing to the fact that today's competitive environment presenting tremendous challenges. In this paper, attempt has been made to identify the key factors influencing the behaviour of investor as perceived by wealth managers of Punjab.